1991
DOI: 10.1007/bf01659055
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant amebic colitis

Abstract: Amebiasis is the acute and chronic disease produced by Entamoeba histolytica, an entity which occurs in endemic fashion in many of the tropical and subtropical areas of the world, capable of affecting diverse organs of the body, especially the colon. Amebiasis has different clinical forms of presentation, varying from the asymptomatic carrier state to severe, although not frequent, fulminant or necrotizing colitis, characteristically associated with high morbidity and mortality. We hereby report a series of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 14 publications
0
49
0
3
Order By: Relevance
“…3,6,8,9 In relation to the clinical findings, the proportion of patients with tenesmus was higher among survivors. The regression model suggests tenesmus as a factor associated with a decrease risk of mortality, while low lymphocyte count had a positive association.…”
Section: Discussionmentioning
confidence: 95%
“…3,6,8,9 In relation to the clinical findings, the proportion of patients with tenesmus was higher among survivors. The regression model suggests tenesmus as a factor associated with a decrease risk of mortality, while low lymphocyte count had a positive association.…”
Section: Discussionmentioning
confidence: 95%
“…Typically, entamebiasis leads to a chronic course, presenting with mucus and blood in the stool. Almost all who contract E. histolytica remain carriers, and approximately 10% present with symptoms of amebic colitis, including bloody and watery diarrhea, and abdominal pain [1,2]. It is reported that about 3% of amebic colitis cases are fulminant type, leading to intestinal perforation or peritonitis [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis of FAC is generally considered challenging, and sometimes a differential diagnosis of inflammatory or infective colitis is necessary. Because FAC is associated with high mortality [2], immediate administration of metronidazole should be considered soon after the condition is suspected or diagnosed. If FAC is suspected from clinical symptoms, and/or social history or travel history, further examination to confirm the condition is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In each report, delay in the diagnosis of amebiasis was associated with poor prognosis, because it is challenging to establish a prompt diagnosis in most situations. Moreover, high mortality after bowel resection in amebic colitis results from difficulties in placing the sutures due to the vulnerability of the intestinal wall (13).…”
Section: Discussionmentioning
confidence: 99%